2019
DOI: 10.1080/2576117x.2019.1624440
|View full text |Cite
|
Sign up to set email alerts
|

Fellow Eye Deficits in Amblyopia

Abstract: Amblyopia is a neurodevelopmental disorder of the visual system, as a result of discordant visual experience during infancy or early childhood. Because amblyopia is typically defined as monocularly reduced visual acuity accompanied by one or more known amblyogenic factors, it is often assumed that the fellow eye is normal and sufficient for tasks like reading and eye-hand coordination. Recent scientific evidence of ocular motor, visual, and visuomotor deficits that are present with fellow eye monocular viewing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 83 publications
(141 reference statements)
1
20
1
Order By: Relevance
“…The FEs of many amblyopes are not as good as those in normally sighted people, because recent scientific evidence showed that ocular motor, visual, and visuomotor deficits were present with fellow eye monocular viewing and with binocular viewing. [57][58][59][60] Training may have general effects on FE acuity. Nevertheless, our results suggest that monocular and dichoptic perceptual learning are both effective in improving AE visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…The FEs of many amblyopes are not as good as those in normally sighted people, because recent scientific evidence showed that ocular motor, visual, and visuomotor deficits were present with fellow eye monocular viewing and with binocular viewing. [57][58][59][60] Training may have general effects on FE acuity. Nevertheless, our results suggest that monocular and dichoptic perceptual learning are both effective in improving AE visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…The discordant binocular experience due to these pediatric eye conditions not only impairs visual acuity in the affected eye but also results in fellow eye deficits and disrupts the development of binocularity (e.g., decreased stereoacuity, interocular suppression). [1][2][3][4] Amblyopia emerges during a critical period of brain maturation and has the potential to affect the performance of real-world tasks that require vision for development, including fine and gross motor skills.…”
mentioning
confidence: 99%
“…We also found the fellow eyes of these patients have slightly higher OCT fixation shift than the control eyes, which confirms that fellow eyes have deficient fixation stability as well. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…We also found the fellow eyes of these patients have slightly higher OCT fixation shift than the control eyes, which confirms that fellow eyes have deficient fixation stability as well. 15,16 Fixation shift is more frequent nasally, including supranasally and infranasally, than other directions in the amblyopic eye, correlating with most of our strabismic patients being esotropic. Garcia-Garcia et al 10 report OCT fixation shift in 15 patients with microtropia, and found that 57% fixation shifts are superior nasal.…”
Section: Oct Fixation Shift Versus Amblyopia Subtypesmentioning
confidence: 96%